The prognostic significance of repeated prehospital shocks for out-of-hospital cardiac arrest survival. Issue 3 (8th November 2018) - Cournoyer, Alexis; Notebaert, Éric; Cossette, Sylvie; Londei-Leduc, Luc; de Montigny, Luc; Ross, Dave; Lamarche, Yoan; Potter, Brian J.; Vadeboncoeur, Alain; Daoust, Raoul; Sokoloff, Catalina; Albert, Martin; et al.
ABSTRACT: Objectives: Patients suffering from an out-of-hospital cardiac arrest (OHCA) associated with an initial shockable rhythm have a better prognosis than their counterparts. The implications of recurrent or refractory malignant arrhythmia in such context remain unclear. The objective of this study is to evaluate the association between the number of prehospital shocks delivered and survival to hospital discharge among patients in OHCA. Methods: This cohort study included adult patients with an initial shockable rhythm over a 5-year period from a registry of OHCA in Montreal, Canada. The relationship between the number of prehospital shocks delivered and survival to discharge was described using dynamic probabilities. The association between the number of prehospital shocks delivered and survival to discharge was assessed using multivariable logistic regression. Results: A total of 1, 788 patients (78% male with a mean age of 64 years) were included in this analysis, of whom 536 (30%) received treatments from an advanced care paramedic. A third of the cohort (583 patients, 33%) survived to hospital discharge. The probability of survival was highest with the first shock (33% [95% confidence interval 30%-35%]), but decreased to 8% (95% confidence interval 4%-13%) following nine shocks. A higher number of prehospital shocks was independently associated with lower odds of survival (adjusted odds ratio=0.88 [95% confidence interval 0.85-0.92], p < 0.001). Conclusion: Survival remains possible even after a high number of shocks for patients suffering from an OHCA with an initial shockable rhythm. However, requiring more shocks is independently associated with worse survival. Résumé: Objectifs: Les patients souffrant d'un arrêt cardiaque extrahospitalier (ACEH) dont le rythme initial est défibrillable sont à meilleur pronostic que si leur rythme initial ne l'est pas. Cependant, l'impact sur la survie de nécessiter de multiples défibrillations demeure incertain. L'objectif de cette étude est d'évaluer l'association entre le nombre de défibrillations préhospitalières et la survie au congé hospitalier chez les patients souffrant d'un ACEH. Méthodes: Des patients adultes avec un rythme initial défibrillable tirés de cinq années d'un registre d'ACEH ont été inclus dans cette étude de cohorte. L'évolution de la survie au congé en fonction du nombre de défibrillations préhospitalières déjà administrées a été décrite à l'aide de probabilités dynamiques. L'association entre le nombre de défibrillations préhospitalières et la survie au congé a été évaluée à l'aide d'une régression logistique multivariée. Résultats: Un total de 1, 788 patients (Homme: 78%; âge moyen: 64 ans) ont été inclus dans l'analyse. Parmi ceux-ci, 536 (30%) ont été traités par des paramédics prodiguant des soins avancés en réanimation. Un tiers de la cohorte (583 patients, 33%) a survécu jusqu'à son congé hospitalier. La probabilité de survie était maximale à la première défibrillation (33% [intervalle de confiance à 95% 30%-35%]), puis diminuait jusqu'à 8% (intervalle de confiance à 95% 4%-13%) suite à neuf défibrillations. Une association entre la mortalité et un nombre plus élevé de défibrillations a été observée (rapport des cotes ajustés=0.88 [intervalle de confiance à 95% 0.85-0.92], p < 0.001). Conclusions: Il demeure possible de survivre à un ACEH même après un grand nombre de défibrillations. Cependant, nécessiter plus de défibrillations est associé à une moins bonne survie pour ces patients.